Real-Time Concurrent Constraint Calculus: The Complete Operational Semantics - Gerardo, M; Sarria, M (Engineering Letters, 2011)
The Real-Time Concurrent Constraint Programming Calculus (rtcc) is a model of concurrency developed to specify systems with real-tune behaviour. In this paper we provide the complete operational semantics of this calculus.